Corporate Social Responsibility in a Changing World: A Review of Empirical Research (2017-2019) - Devi Anastasya; Harefa, Vilisna Angelika; Jeremy Juan Carol (Draf Solusi Indonesia, 2025)
This systematic literature review aims to synthesize empirical research on Corporate Social Responsibility (CSR) published between 2017 and 2019, addressing gaps in understanding how CSR is conceptualized, measured, and implemented amid evolving global expectations and digitalization. Using a systematic review methodology, we analyzed peer-reviewed empirical studies sourced from major academic databases, focusing on variables such as CSR’s impact on financial performance, stakeholder perceptions, and internal organizational factors. The review process involved rigorous screening and extraction of studies meeting strict inclusion criteria. Results indicate a consistently positive relationship between CSR and financial performance, with stakeholder engagement and organizational culture as key mediators. These findings refine CSR theory and offer actionable insights for both scholars and practitioners.